The Evaluation of Androctonus crassicauda Antivenom against the Effects of Aegaeobuthus nigrocinctus Scorpion Venom on Autophagy, Apoptosis and Necroptosis - Mehmet Eray Alcıgır; Ozcan Ozkan (Tehran University of Medical Sciences, 2023)
Background: In this study aimed to show the role of autophagy acting as a seesaw between apoptosis and necroptosis in certain vital organs under the effects of the Aegaeobuthus nigricinctus venom and different dosages of the Androctonus crassicauda antivenom administration in mice. Methods: In the venom group (VG), mice (n= 6) were inoculated with 2LD50 A. nigrocinctus venom. In the antivenom administered groups (AVG), the effects of the potency of the A. crassicauda antivenom were evaluated to have a neutralization effect against 20LD50 of the A. nigrocinctus venom. After histopathological examination, expressions of mammalian target of rapamycin (mTOR) as an autophagy activator, receptor-interacting serine/threonine-protein kinase 3 (RIPK3) as a necroptosis activator, and caspase-3, caspase-9 as the markers of apoptotic cell death signals were evaluated by the immunoperoxidase method in addition to DNA in-situ fragmentations by the terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) method. Results: Only in VG, caspases and TUNEL expressions were found to be higher after the envenomation process in contrast to the elevated RIPK3 expressions. mTOR expressions remained almost stable in the organs. In AG, mTOR expressions were further increased in the 30LD50 and 40LD50 groups. Conclusion: There were an increased mTOR expression and stabilized caspases and TUNEL expression in these subgroups, the RIPK3 expressions were found to be low when compared with all of the antivenom administration groups. Increasing doses of the antivenom drifts more the cells to autophagy while cell fate in organs under envenomation getting rid of apoptosis and necroptosis pathways.